Strategi Keamanan Siber Nasional Qatar (Qatar’s National Cyber Security Strategy) - Silvia, Anggraeni; Muhajirin, Adi (Jurnal Keamanan Nasional, 2021)
Along with the development of technology, cyber threats that occur in modern countries has been switched from traditional to non-traditional. That development of technology bears the advancement of science and bring a variety of the interstate. Currently, the country prioritizes in social, economic, law, security, defense and other aspect to Information and Communication Technology. Increasing the cyber threat of Qatar, the governance draws up National Cyber Security Strategy (NCSS) with the aim of building andmaintaining a safe cyberspace for protecting national interest and preserves fundamental rights and Qatar’s community value. Collectively this aim gives protection and preparing cyber threats with proactive approach. This paper aims to deeply understand Qatar National Cyber Security Strategic by conducting a qualitative analysis of the context of document through the concept ofsovereignty approach, nation and contained aspects. The description of aspects that can be seen from the data security relationship, technology development, policies, capabilities, strategic approaches, cyber threats and challenges. Qatar pays special attention to cybersecurity and protection of its vital national information infrastructure as dependence on Information and Communication Technology (ICT) and the internet grows in the country.